Outcome of Acquired Aphasia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1991)
The effects of age at onset, etiology, severity, and type of aphasia on the course and outcome were investigated in a group of 28 aphasic children at the Department of Neurology, University Hospital Rotterdam-Dijkzigt, the Netherlands.